DINAMIKA KAJIAN LIVING QUR’AN DI INDONESIA: SEBUAH PENYEMPURNAAN - Sofia Mawaddah Al Insyirah (Al Arsy: Journal of Education, Management and Islamic Thought, 2026)
Originating from the phenomenon of "the Qur’an in everyday life," the Living Qur’an has now become a prominent trend among scholars of Qur’anic studies. In Indonesia, this field of study highlights how the Qur’an lives within a non-Arabic-speaking society that nevertheless shows great enthusiasm for placing the Qur’an in its rightful position—as a guide for life. Thus far, the Living Qur’an is considered to lack a solid epistemological framework to be classified as a distinct method. As a result, many of its applications are deemed to have shifted too far into socio-anthropological discussions rather than focusing on the Qur’anic phenomenon itself. This paper explicitly re-examines the Living Qur’an as an established theory and methodology within Qur’anic studies, exploring how it should be utilized as an integral part of the Qur’anic phenomenon. The concept of the Living Qur’an as a scholarly study regarding the presence of the Qur’an in a specific Muslim community requires careful attention to ensure that the scope of research remains focused on the Qur’an. This can be achieved by outlining the functions of the Qur’an as received by a community, and by observing the transmission and transformation of meaning into tradition, thereby producing an objective appreciation of society's responses and behaviors toward the presence of the Qur’an.